2010
DOI: 10.1186/1472-6920-10-76
|View full text |Cite
|
Sign up to set email alerts
|

Learning health professionalism at Makerere University: an exploratory study amongst undergraduate students

Abstract: BackgroundAnecdotal evidence shows that unprofessional conduct is becoming a common occurrence amongst health workers in Uganda. The development of appropriate professional values, attitudes and behaviors is a continuum that starts when a student joins a health professional training institution and as such health professionals in training need to be exposed to the essence of professionalism. We sought to explore undergraduate health professions students' perceptions and experiences of learning professionalism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 39 publications
(64 reference statements)
5
62
0
3
Order By: Relevance
“…This entitlement to patient information is often associated with particular settings as similar findings were reported in Uganda and elsewhere in Africa. [20] Compassion and care BCMP students reflected on the value of demonstrating compassion and care in the clinical setting as an attribute mainly observed in Paeds similar to findings reported in two studies conducted in the USA. [11,12] The positive reflections that BCMP students experienced in Paeds were consistent with and met the recommendations of the HPCSA that require HCPs to always show regard for their patients as their primary professional duty.…”
Section: Confidentialitysupporting
confidence: 67%
See 1 more Smart Citation
“…This entitlement to patient information is often associated with particular settings as similar findings were reported in Uganda and elsewhere in Africa. [20] Compassion and care BCMP students reflected on the value of demonstrating compassion and care in the clinical setting as an attribute mainly observed in Paeds similar to findings reported in two studies conducted in the USA. [11,12] The positive reflections that BCMP students experienced in Paeds were consistent with and met the recommendations of the HPCSA that require HCPs to always show regard for their patients as their primary professional duty.…”
Section: Confidentialitysupporting
confidence: 67%
“…The experiences of the students are supported by Tsotsi [19,20] who refers to the process of attaining informed consent in developing countries as a complex issue or a contentious issue that is context-specific. [20] Truth-telling BCMP students observed that for many of the adolescents, poor communication between HCPs and the patients was contrary to the best interests of the patients. The dilemma around the issue of trust that students faced was based on the fact that there was no consensus, e.g.…”
Section: Box 1 Hatem's Definition Of Professionalismmentioning
confidence: 99%
“…In Pakistan, Humayun et al 17 found that there was a striking lack of awareness of these principles, potentially due to the paternalistic model of patient care in many Asian cultures. Baingana and colleagues 18 reported that in Uganda, the community-centric Ubuntu philosophy ran contrary to the established Western notion of confidentiality. In Confucian-influenced societies, ideas are not considered to belong to the original author, but rather are part of society's collective knowledge, and reproducing ideas is perceived as being respectful to the owner rather than plagiarism.…”
mentioning
confidence: 99%
“…30 Dispensing is a task that physicians are expected to do but are not trained to do. The role of the hidden curriculum has been explored in the sphere of undergraduate medical education, 43 with areas such as professionalism 44,45 and ethics 46,47 receiving particular attention. The 100-year anniversary of the Flexner report into postgraduate medical education in the United States has recently transferred attention on the curriculum in this area, 48,49 with a refocusing on preparing physicians to work safely and effectively ahead of encyclopedic scientific knowledge.…”
Section: Discussionmentioning
confidence: 99%